Effect of the temperature and osmotic stress on the growth and cell viability of Candida maltosa - Bhuiyan, Mohammad Nazrul Islam; Raiyaan, KR; Afrin, Sadia; Nahid, Meher (Bangladesh Journal of Scientific and Industrial Research, 2023)
The present research attempted to observe the temperature and osmotic stress effects on yeast species in cheese. The Candida maltosa yeast was isolated from locally made raw cheese samples, and it was identified by its biochemical properties, followed by using the BIOLOGTM microbial identification system to confirm species level identification. The study investigate about Candida maltosa's ability to grow and develop a budding pattern under high temperatures up to 44°C and osmotic stress for 72 h. Osmotic stress tolerance was studied at 32.5°C in different concentrations of dextrose (0.04 g/l, 0.12 g/l, 0.2 g/l, 0.28 g/l, and 0.36 g/l) and sucrose (0.02 g/l, 0.06 g/l, and 0.36 g/l), respectively. Cell growth of the C. maltosa was measured by optical density at 600nm (OD600) and the enumeration of colony forming units (CFUs) on the agar plates up to 300 m. The obtained result indicated the optimal growth pattern at 32.5°C and complete growth retardation at 44°C with the high concentrations of dextrose (0.36 g/l) and sucrose (0.38 g/l). Particularly, C. maltosa budding could only survive 240 m at 37°C to 40°C and was suppressed at 44°C. The experimental findings demonstrated the stress response in yeast cells in the phenotypic level with the existing acquaintance on the osmotic stress response actions in C. maltosa. Bangladesh J. Sci. Ind. Res. 58(2), 71-78, 2023